EVALUASI PROGRAM REHABILITAS RUMAH TIDAK LAYAK HUNI (RTLH) TAHUN 2019 DI KABUPATEN OGAN KOMERING ULU - Tia Putri; Aprilia Lestari; Eva Susanti (Jurnal Ilmu Pemerintahan, 2024)
The Uninhabitable House Rehabilitation Program is a government program that aims to help low-income people have habitable houses. The problems with this program are limited quotas, lack of contribution in providing building materials, and lack of clarity when conveying building distribution procedures. This program needs to be evaluated to find out the results of the 2019 Uninhabitable House Rehabilitation Program in Ogan Komering Ulu Regency which has been implemented.This research was carried out on 14-30 October 2023. The theory used was Policy Evaluation Theory according to William Dunn with indicators of effectiveness, adequacy, equity, responsiveness and accuracy. Qualitative descriptive research method. Data collection techniques through observation, interviews and documentation. Data analysis techniques by collecting data, reducing data, presenting data, and drawing conclusions.Based on the research results of five indicators, namely: 1) Effectiveness, it has been implemented effectively as expected. 2) Sufficiency, this program is sufficient to solve problems and the funds/materials provided are also sufficient. 3) Equity, development implementation has been even and there are no longer any people who have houses that are uninhabitable. 4) Responsiveness, this program has been very responsive as seen so far the response from the community, sub-districts and the Perkim Service has been good. 5) Accuracy, this program is right on target because this program is really given to people who have low incomes and have uninhabitable houses.This research can be concluded that the 2019 Uninhabitable House Rehabilitation Program in Ogan Komering Ulu Regency has been able to achieve its goal of solving the problem of uninhabitable houses.